2017
DOI: 10.3389/fnagi.2017.00198
|View full text |Cite
|
Sign up to set email alerts
|

Variants in SNCA Gene Are Associated with Parkinson’s Disease Risk and Cognitive Symptoms in a Brazilian Sample

Abstract: Genetic susceptibility contributes to the etiology of sporadic Parkinson’s Disease (PD) and worldwide studies have found positive associations of polymorphisms in the alpha-synuclein gene (SNCA) with the risk for PD. However, little is known about the influence of variants of SNCA in individual traits or phenotypical aspects of PD. Further, there is a lack of studies with Latin-American samples. We evaluated the association between SNCA single nucleotide polymorphisms (single nucleotide polymorphisms, SNPs – r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 114 publications
1
21
0
1
Order By: Relevance
“…Association of the SNCA rs356219 A allele and MF is an unexpected finding because this variant has been associated with reduced PD susceptibility and older age at onset, [29][30][31] as well as reduced plasma α-synuclein levels in PD. 32 Our observed association may reflect less severe diffuse α-synuclein pathology in levodoparesponsive patients who develop early MF, but it is a finding that requires further replication in an independent cohort.…”
Section: Discussionmentioning
confidence: 98%
“…Association of the SNCA rs356219 A allele and MF is an unexpected finding because this variant has been associated with reduced PD susceptibility and older age at onset, [29][30][31] as well as reduced plasma α-synuclein levels in PD. 32 Our observed association may reflect less severe diffuse α-synuclein pathology in levodoparesponsive patients who develop early MF, but it is a finding that requires further replication in an independent cohort.…”
Section: Discussionmentioning
confidence: 98%
“…Yet single nucleotide polymorphisms (SNPs) in the SNCA and the microtubule‐associated protein Tau ( MAPT ) genes have shown top‐hit association signals with PD risk in genomewide association studies and in candidate gene studies . For instance, the SNP rs356219 in the 3’ untranslated region (3’‐UTR) of SNCA is a haplotype‐tag SNP associated with a higher risk of PD and related to increased SNCA protein expression . This tag SNP also modulates AAO in both IPD and leucine‐rich repeat kinase 2 (LRRK2)–associated PD (L2PD) .…”
mentioning
confidence: 99%
“…Parkinson's disease (PD), the second most common neurodegenerative disease after Alzheimer's disease, affects approximately 1-2% of individuals over 65 years of age [11,12]. The incidence of PD usually begins after 50 years of age and increases more after 60 years of age [13]. The prevalence of PD increases approximately 4% in people over 85 years of age [6].…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…In a study conducted in the United States, it was found that some single-nucleotide gene polymorphisms in the SNCA gene were associated with the risk of PD development, but no significant relationship was determined between rs11931074 gene polymorphism and PD development risk [46]. In a study conducted with a South American Brazilian population, the relationship between rs2583988, rs356219, rs2736990, and rs11931074 gene polymorphisms and the risk of PD development was investigated, and the significant relationship was determined between rs356219 gene polymorphism and increased cognitive disorder in PD patients [13]. In studies conducted with European and North American populations, rs2736990 gene polymorphism has been identified as a genetic risk factor in PD development [47].…”
Section: Gene Polymorphisms Of Sncamentioning
confidence: 99%
See 1 more Smart Citation